Exploring Hotel Tax Potential In Pesangrahan District - Prastya, Heru; Firmansyah, Amrie (WIM Solusi Prima, 2024)
Bapenda DKI Jakarta achieved the revenue target of 5 local taxes out of 13 types of taxes it administers in 2022. Of the five types of local taxes, the Hotel Tax is the only tax administered in all UPPPDs. However, in 2022, the UPPPD of Pesanggrahan District failed to achieve its Hotel Tax revenue target. The challenge in 2024 became more severe due to the withdrawal of the authority to collect some Hotel Tax objects from the Local Government. This study analyzes the potential exploration of several Hotel Tax objects in Pesanggrahan District through a micro approach. Data analysis was conducted using the quantitative method. Based on the analysis that utilizes Room Occupancy Rate (TPK) of star-rated hotels data from BPS, this study obtained the results of the potential value of Hotel Tax for Arosa Hotel during the 2023 tax year amounting to IDR 1.738.509.520. In addition, this research also obtained the results of extracting the potential of Hotel Tax on three boarding houses in Pesanggrahan District in October 2023, amounting to IDR 22.415.000. The results of this study are expected to be an input for UPPPD of Pesanggrahan District in extracting the potential of Hotel Tax in its area. Using external data such as TPK of starred hotels from BPS and room occupancy rates from boarding house provider websites can be an alternative for UPPPD of Pesanggrahan District in exploring the potential of Hotel Tax besides analyzing the trend of taxpayer deposits.